-9g+13g=-12

Simple and best practice solution for -9g+13g=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9g+13g=-12 equation:


Simplifying
-9g + 13g = -12

Combine like terms: -9g + 13g = 4g
4g = -12

Solving
4g = -12

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by '4'.
g = -3

Simplifying
g = -3

See similar equations:

| 4log^10(3x)=8 | | 2x+12x-2=0 | | -10=b/7 | | 3v+12=-15forv | | 13x+15=1x-25 | | 7/3x+1/3x=3x+12/3+5/3x | | -3x-2x+1=16 | | 1/4x=20 | | -7x-6(2x+10)=-115 | | 4r+r+2r-5-4r+10=r | | -5y-(15y-1)=2(7y-16)-y | | 8x^2+2x+12=3x^2+11x+19 | | 7n-5n-n=8 | | 163x(377)+95=377 | | 12/3*41/2 | | 4x+2x+10=-14 | | -17c+7c+14c-5c+5c=20 | | -9-2+8*-2=-23 | | W-5.3=7.6 | | -5(6-n)+1=3n-5(n-4) | | 4x-3(5-x)=7x-15 | | 3x^2-10=26 | | -3/4x=-12 | | -3b=-2-3b | | x-9x+3=17 | | (5/3)x-11=18/7 | | (x-1)^2/3 | | X-21=54 | | 7.75x=434 | | (5)/(7)x=-(9)/(14) | | 2k-k=16 | | .6(x+.6)=5.7 |

Equations solver categories